2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793676
|View full text |Cite
|
Sign up to set email alerts
|

Manipulability Optimization Control of a Serial Redundant Robot for Robot-assisted Minimally Invasive Surgery

Abstract: This paper proposes a manipulability optimization control of a 7-DoF robot manipulator for Robot-Assisted Minimally Invasive Surgery (RAMIS), which at the same time guarantees a Remote Center of Motion (RCM). The first degree of redundancy of the manipulator is used to achieve an RCM constraint, the second one is adopted for manipulability optimization. A hierarchical operational space formulation is introduced to integrate all the control components, including a Cartesian compliance control involving the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The autonomous laparoscope control is regarded as the principal task and guarantees the safety‐RCM constraint. Therefore, under the null‐space framework and according to the previous studies, it can be concluded that the torque τ R required to ensure the RCM constraint is shown in Equation . τR=NRJnormalRTαRitalicΔd+βRΔd˙. …”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The autonomous laparoscope control is regarded as the principal task and guarantees the safety‐RCM constraint. Therefore, under the null‐space framework and according to the previous studies, it can be concluded that the torque τ R required to ensure the RCM constraint is shown in Equation . τR=NRJnormalRTαRitalicΔd+βRΔd˙. …”
Section: Methodsmentioning
confidence: 90%
“…Therefore, under the null-space framework and according to the previous studies, [22][23][24] it can be concluded that the torque τ R required to ensure the RCM constraint is shown in Equation (6).…”
Section: Framework Of Autonomous Laparoscope Controlmentioning
confidence: 91%
“…To guarantee control frequency, force sensor, ROS node and OROCOS torque controller were executed on separate computers with UDP communication [41] between each other: the control loop and the sensing ROS node was executed on separate computers, as shown in Figure 8. The system consists of: a seven DoFs LightWeight robotic arm (LWR4+, KUKA, Augsburg, Germany) as slave device.a six-axis force sensor (M8128C6, SRI, Nanning, China) [42] that has the purpose of measuring interaction force between the surgical tool-tip and the environment.…”
Section: Experimental Validation and Resultsmentioning
confidence: 99%
“…a six-axis force sensor (M8128C6, SRI, Nanning, China) [42] that has the purpose of measuring interaction force between the surgical tool-tip and the environment.…”
Section: Experimental Validation and Resultsmentioning
confidence: 99%
“…A Kano model analysis is conducted and the TRIZ theory is utilized to redesign a novel rollator for meeting the requirements of the elderly. Compared to the designed rollator in the state of art [3,[37][38][39], the novel rollator is more suitable for elderly users, featured with a simple geometric shape, the adjustable seat, and suitable materials, etc.…”
Section: Resultsmentioning
confidence: 99%